2001
DOI: 10.1128/aem.67.9.3866-3872.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Viable But Nonculturable State of Ralstonia solanacearum May Be Involved in Long-Term Survival and Plant Infection

Abstract: The role of the dormant-like viable but nonculturable (VBNC) condition in the etiology of bacterial infection was examined using a plant system. The plant-pathogenic bacterium Ralstonia solanacearum was first shown to enter into the VBNC state both in response to cupric sulfate when in a saline solution and when placed in autoclaved soil. To determine if the VBNC condition is related to pathogenesis, the physiological status of bacteria recovered from different regions of inoculated tomato plants was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(131 citation statements)
references
References 31 publications
5
121
1
4
Order By: Relevance
“…Under prolonged oligotrophy, reduction in cell size and change to a round cell shape are also considered as bacterial strategies to survive in the environment (Novitsky & Morita, 1976;Rollins & Colwell, 1986;Ruiz et al, 2001), as well as the induction of a viable but non-culturable (VBNC) state (Oliver, 2005;Roszak & Colwell, 1987) that constitutes a distinct physiological state from that of the starvation response (Heim et al, 2002). R. solanacearum becomes VBNC by exposure to copper (Grey & Steck, 2001) and after incubation at low temperature in soil and water (Caruso et al, 2005;van Elsas et al, 2000van Elsas et al, , 2001van Overbeek et al, 2004). Adaptations to oligotrophy have not previously been described for R. solanacearum.…”
Section: Introductionmentioning
confidence: 99%
“…Under prolonged oligotrophy, reduction in cell size and change to a round cell shape are also considered as bacterial strategies to survive in the environment (Novitsky & Morita, 1976;Rollins & Colwell, 1986;Ruiz et al, 2001), as well as the induction of a viable but non-culturable (VBNC) state (Oliver, 2005;Roszak & Colwell, 1987) that constitutes a distinct physiological state from that of the starvation response (Heim et al, 2002). R. solanacearum becomes VBNC by exposure to copper (Grey & Steck, 2001) and after incubation at low temperature in soil and water (Caruso et al, 2005;van Elsas et al, 2000van Elsas et al, , 2001van Overbeek et al, 2004). Adaptations to oligotrophy have not previously been described for R. solanacearum.…”
Section: Introductionmentioning
confidence: 99%
“…Ralstonia solanacearum (Smith) Yabuuchi et al is a soilborne phytopathogenic bacterium characterized by the three following features: i) vast geographical distribution; it is distributed from tropical to temperate regions of the world, 1) ii) very extensive host range; it attacks several hundred species in 44 families of plants, 1) and iii) high viability in soil; it can survive in soil in a viable but nonculturable state 2) or in the weed rooting zone after crop harvesting and the survivors can inflict damage on the next crop planted. 3) We screened native plants in Okinawa that inhibit the growth of R. solanacearum to develop a method to control bacterial wilt of potato, and found that an extract of aerial tissue of Geranium carolinianum showed strong inhibitory activity against R. solanacearum, 4) and that plowing-in of the dried plant was effective to control the bacterial wilt of potato.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these products have a toxic or bacteriostatic effect, only preventing the multiplication of bacteria and most bacteria may die due to the toxic effects of Cu ++ ions, or enter in the VBNC (Viable But Non Culturable) state in which they are unable to grow on solid medium. This state could be induced by copper ions, as previously reported for several plant pathogenic bacteria (Alexander et al, 1999;Grey & Steck, 2001;Ordax et al, 2005). These preventive chemical treatments are recommended for both to reduce epiphytic Psv populations and prevent their penetration through the plant wounds.…”
Section: Direct Controlmentioning
confidence: 67%